Anorectal incontinence and rectal prolapse: differential assessment of the innervation to puborectalis and external anal sphincter muscles. Issue 5 (May 1985) - Snooks, S J; Henry, M M; Swash, M
Abstract : The innervation of the puborectalis and external anal sphincter muscles was studied in 32 patients with idiopathic (neurogenic) faecal incontinence, 12 of whom also had complete rectal prolapse, using transcutaneous spinal stimulation, transrectal pudendal nerve stimulation, single fibre EMG, anorectal manometry, and measurement of perineal descent. Fourteen normal subjects served as controls. Significant increases in the spinal motor latencies from L1 to the puborectalis and external anal sphincter muscles were shown in all 32 incontinent patients (p less than 0.01). The single fibre (EMG) fibre density was increased in the puborectalis muscle in 60% and in the external anal sphincter in 75% of patients. An increased pudendal nerve terminal motor latency was found in 68% of patients; 69% had an abnormal degree of perineal descent and all had reduced anal canal contraction pressures. These data show that the different innervations of the puborectalis and external anal sphincter muscles are both damaged in patients with anorectal incontinence.